Comprehensive Review of Cultural Entrepreneurship Initiatives : Insights from TVET Programmes Empowering Girls - Rajora, Rashmi Kumari; Yadav, Renu (JOURNAL OF INDIAN EDUCATION, 2024)
Cultural entrepreneurship is a growing field that combines entrepreneurial pursuits with cultural aspects to produce commercially feasible goods and services. This study explores the relationship between cultural entrepreneurship and technical and vocational education and Training (TVET) programmes, focusing on empowering girls in India. TVET programmes provide essential knowledge and skills and when combined with cultural entrepreneurship, they offer females new opportunities to use their cultural legacy for economic development. The study uses a multimodal approach to assess the integration of cultural entrepreneurial activities within TVET programmes, focusing on empowering girls in India. Theoretical foundations emphasise the intersection of cultural legacies and entrepreneurial pursuits, emphasising TVET’s role in providing real-world experience and business aptitude. TVET programmes foster gender equality, inclusive policies, career diversity, and entrepreneurship, promoting economic growth and preserving cultural heritage. National educational policies like the National Education Policy (NEP) 2020 and National Policy on Skill Development and Entrepreneurship (NPSDE) 2015 align with the integration of cultural entrepreneurship into TVET, addressing difficulties in scaling skill development and satisfying market demands. Despite obstacles like gender stereotypes, curriculum relevance and access to high-quality education, TVET programmes provide opportunities for empowerment through entrepreneurship, skill development, gender-inclusive policies and teamwork. Investment and cooperative efforts are crucial for successful cultural entrepreneurship activities within TVET programmes and ensuring girls reach their full potential as cultural entrepreneurs, contributing to national prosperity and sustainable development.